Development of automatic weaving technique of tapered circular tubular woven graft: a preliminary validation. Issue 8 (3rd August 2019) - Meng, Fenye; Li, Yuling; Ma, Yanxue; Chen, Xiaoying
Abstract: The tapered circular tubular (TCT) woven fabric has been applied successfully as the components in vascular prostheses. The application of tapered tubular woven fabric based on the existing weaving technology requires the densification of a large end to ensure porosity uniformity through the tapered tubule. Although the previously proposed equal-cover-factor (ECF) design technique overcame some disadvantages of the conventional densification methods, such as the protruding portions of the dropped yarns as well as the change of both fabric porosity and tensile strength, the off-loom weft density significantly deviates from the on-loom value. On the basis of ECF design technique and the basic shed geometry, this study rebuilt the relative motion relationship among the front rest, the cloth fell, the back rest, and the take-up length, and modified the weft density on loom to achieve continuous weaving process of TCT fabric as well as the uniform porosity. And then, a computerized weaving procedure based on the rebuilt relationship was developed to automatically weave TCT fabric with different weaves on the customized shuttle loom. As a result, the uniform porosity of those samples validated the proposed weaving techniques.